1993
DOI: 10.1002/app.1993.070491203
|View full text |Cite
|
Sign up to set email alerts
|

Ionotropic crosslinking of sodium carboxymethylcellulose and sodium carboxymethylcellulose‐gelatin matrices and their erosion properties

Abstract: SYNOPSISHydrophilic sodium carboxymethylcellulose ( NaCMC ) matrices were chemically modified into hydrophobic gels by ionotropic crosslinking with cupric or ferric ion under ambient temperature and pH. Insoluble matrices were also prepared using an interactive polymer gelatin in combination with NaCMC. These matrices underwent erosion at the crosslinks, followed by matrix erosion when released in water. The matrix erosion in water was influenced by the gelling agent, initial crosslinker density, and gelatin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This could be attributed to rigid foam substance in cross-linked formulation. Cross-linking further delay the erosion of gelatin in dissolution medium and further a stable micro porous structure reduces the permeability of dissolution medium, thereby delay the release of entrapped curcumin (Prasad & Kalyanasundaram, 1993) whereas the foam without cross-linking agent was more soluble and permeable to dissolution medium allow faster release of entrapped drug. Release study further confirmed that formaldehyde causes extensive cross-linking of gelatin foam and thereby prove the mechanical stability of foam.…”
Section: In Vitro Drug Releasementioning
confidence: 99%
“…This could be attributed to rigid foam substance in cross-linked formulation. Cross-linking further delay the erosion of gelatin in dissolution medium and further a stable micro porous structure reduces the permeability of dissolution medium, thereby delay the release of entrapped curcumin (Prasad & Kalyanasundaram, 1993) whereas the foam without cross-linking agent was more soluble and permeable to dissolution medium allow faster release of entrapped drug. Release study further confirmed that formaldehyde causes extensive cross-linking of gelatin foam and thereby prove the mechanical stability of foam.…”
Section: In Vitro Drug Releasementioning
confidence: 99%
“…[5][6][7] Formulations were also prepared with an interactive polymer gelatin in combination with carboxymethy l~e l l u l o s e .~~~…”
Section: Oo-dimethyl-o-4-methylthio-m-tolyl-mentioning
confidence: 99%